Brazilian Society of Surgical Oncology surgical standards for resectable colorectal cancer liver metastases. Issue 1 (11th June 2022) - Vaz da Silva, Diego G.; Bredt, Luis C.; Diniz, Alessandro L.; Vieira, Victor H. R.; Fernandes, Paulo H. S.; Ribeiro, Reitan; Ribeiro, Héber S. C.; Oliveira, Alexandre F.
Abstract: The management of colorectal cancer liver metastasis (CRLM) has become complex because of the increasing availability of medical, radiological, and surgical treatment options applied either alone or in combination. However, resection remains the only evidence‐based curative therapy. These Brazilian Society of Surgical Oncology surgical standards are intended to guide clinicians in the decision‐making process for modern surgical management of CRLM within a multidisciplinary team in an evidence‐based framework, focusing on resectable disease.